Feministiese hermeneutiek as kritiese teorie - Dreyer, Yolanda (Hervormde teologiese studies, 1998)
Feminist hermenentics as citical theory. The aim of this study is to descibe the main characteistics of some approaches within feminist hermeneutics. The following approaches have been idenified by Carolyn Osiek: 'rejeciorust', 'revisionist', 'sublimationist' and 'liberationist'. To these approaches an epistemology of paricipation is added. Feminist hermeneuics is seen through the lense of the citical theory of Jürgen Habermas. The result poses an alternative to a positivistic approach to Scripture. Some contibuions of feminist hermeneuics to church and society are idenified.